CB1 and LPA1 Receptors Relationship in the Mouse Central Nervous System - González de San Román, Estíbaliz; Manuel, Iván; Ledent, Catherine; Chun, Jerold; Rodríguez de Fonseca, Fernando; Estivill-Torrús, Guillermo; Santín, Luis Javier; Rodríguez Puertas, Rafael (Frontiers in Molecular Neuroscience, 2019)
Neurolipids are a class of bioactive lipids that are produced locally trough specific biosynthetic pathways in response to extracellular stimuli. Neurolipids are important endogenous regulators of neural cell proliferation, differentiation, oxidative stress, inflammation and apoptosis. Endocannabinoids and lysophosphatidic acid are examples of this type of molecule and are involved in neuroprotection. The present study analyzes a possible relationship of the main receptor subtypes for both neurolipid systems that are present in the central nervous system, the CB1 and LPA1 receptors, by using brain slices from CB1 KO mice and LPA1-null mice. Receptor-mediated G protein activation and glycerophospholipid regulation of potential precursors of their endogenous neurotransmitters were measured by two different in vitro imaging techniques, functional autoradiography and imaging mass spectrometry, respectively. Possible crosstalk between CB1 and LPA1 receptors was identified in specific areas of the brain, such as the amygdala, where LPA1 receptor activity is upregulated in CB1 KO mice. More evidence of an interaction between both systems was that the CB1-mediated activity was clearly increased in the prefrontal cortex and cerebellum of LPA1-null mice. The endocannabinoid system was specifically over-activated in regions where LPA1 has an important signaling role during embryonic development. The modifications on phospholipids observed in these genetically modified mice by using the IMS technique indicated the regulation of some of the phospholipid precursors of both lysophosphatidic acid and endocannabinoids in specific brain areas. For example, phosphatidylcholine (36:1) was detected as a potential lysophosphatidic acid precursor, and phosphatidylethanolamine (40:6) and phosphatidylethanolamine (p18:0/22:6) as potential endocannabinoid precursors. The absence of the main cerebral receptors for lysophosphatidic acid or endocannabinoid systems is able to induce modulation on the other at the levels of both signaling and synthesis of endogenous neurotransmitters, indicating adaptive responses between both systems during prenatal and/or postnatal development.